The Social and Political Factors on the Decision-Making Process in Land Acquisition for Sicincin-Padang Toll Road Construction, West Sumatera - Nora Eka Putri; Helmi Helmi; Melinda Noer; Yossyafra Yossyafra (Faculty of Social Science, Universitas Negeri Padang, 2023)
Land acquisition for the construction of toll roads is a key component of growth, however property acquisition has run into challenges. One of these challenges is that there hasn't been an adequate amount of community involvement and social and political studies of the impacted communities, which puts the community at risk while also impeding the efficient building of toll roads. With the use of the variables of community culture, political will, land governance, and community involvement in the decision-making process, this study tries to explain the elements that affect the decision-making process in land acquisition planning. The research strategy is a quantitative. 325 respondents completed questionnaires distributed to the impacted neighborhoods, which were used to gather research data. The data was then analyzed using structural equation models (Structural Equation Models) utilizing the AMOS application and the Sobel test. According to the study's findings, the decision-making process was significantly influenced by community culture, political will, and land governance. In light of community cultural characteristics such as political will, land governance, and community involvement, the study's conclusion shows that a model for land acquisition policy decision-making exists.